Remembering radio. (1st April 2013) - Lewis, Peter
The article concerns a part of a wider project, 'A Remembered Soundscape', in which I am attempting to recapture the sounds of my childhood and to write about them as, what Murray Shafer has called, an 'earwitness'. The focus here is on the remembered experience of radio listening over two decades between the late 1930s and the late 1950s, a time when 'the wireless' was the most significant source of mediated sound. Memories of listening in the setting of the home are compared with the contemporary experience of encountering archival recordings. An added motivation for the project is the challenge of trying to develop the limited vocabulary that relates to sound.Since 'memory is partial' (Kuhn) and 'what it contrives symptomatically to forget is as important as what it remembers' (Samuel), recall is checked against family and public documentation – family diaries and letters, and records in Mass Observation Archive. Examples are given of remembered radio programmes and the everyday domestic context within which they were first heard and embedded. The pace, accent and intonation of these examples, heard in the present day, are what are found most alien in this exercise in self-ethnography.